Equity crowdfunding - A Finnish case study - Lasrado, L.; Lugmayr, Artur (IEEE, 2014)
Crowdfunding grows at rapid pace internationally, and global platforms like Kickstarter and Indegogo are main leaders of this trend. Within the scope of this paper, we investigate the case of crowdfunding in Finland and identify particular national needs and potential what this new phenomenon has. The phenomenon of the Crowdfunding has been growing at a rapid pace in Finland, with it being seen as fundraising and effective marketing tool. Especially start-ups have started using the power of the crowd to promote their ideas and products as well as to raise funding. They are very opened to use Crowdfunding as an additional source of finance during their first round of financing. The effect of global platforms like Kickstarter and Indegogo, and in addition successful national ventures like Timo Vuorensola's campaigns for the new movie Iron Sky popularised Crowdfunding in Finland demonstrates the power of this instrument. In particular the younger audience is opened for this new tool. Within the scope of this paper we analyse the power of Crowdfunding in the Finnish context based on a literature study, and analysis of data gathered from Crowdfunding platforms.